PENDEKATAN ARSITEKTUR KOSMOLOGI BALI DAN PRAGMATIC UTOPIA DALAM MERANCANG KONSERVASI TERUMBU KARANG DI PULAU NUSA PENIDA - Nicholas Gabriel; J.M. Joko Priyono Santosa (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The life of the marine ecosystem is starting to be threatened by the natural phenomena that occur, destroying marine life and coral reefs. The destruction of coral reefs begins with the occurrence of bleaching. This phenomenon can quickly kill coral reefs extensively in less than a year and cause the death of marine life in coastal ecosystems. The theory adopted uses the concept of Balinese cosmology and pragmatic utopia in responding to the challenge of going beyond ecology and responding to the context of the surrounding environment. The selected program is a conservation function and a gallery for visitors to explore the space within the site. This project creates a new formula for balancing traditional theory with the utopia of the future. The concept of Balinese cosmology is applied in the layout of the space according to the beliefs of the Balinese people. This project is expected to be a hope and a public space that conveys the experience of spatial space bringing people into a different dimension, appreciating the exploration process. Become a project that can influence visitors psychologically on the importance of the survival of marine ecosystems. Keywords: Coral reefs; Conservation; Cosmology; Pragmatic Utopia; Spatial space AbstrakKehidupan ekosistem laut mulai terancam dengan fenomena alam yang terjadi membuat biota laut beserta terumbu karang hancur. Kehancuran terumbu karang dimulai dari terjadinya bleaching. Fenomena ini dapat dengan cepat membunuh terumbu karang secara luas kurang dari setahun dan menyebabkan kematian biota laut pada ekosistem pesisir pantai. Teori yang diangkat menggunakan konsep kosmologi Bali dan pragmatic utopia dalam menjawab tantangan untuk malampaui ekologi dan menanggapi konteks lingkungan sekitar. Program yang dipilih merupakan fungsi konservasi dan gallery untuk pengunjung menjelajahi ruang dalam site. Proyek ini menciptakan formula baru dalam menyeimbangkan teori tradisional dengan utopia masa depan. Konsep kosmologi Bali diterapkan dalam tata letak ruang sesuai kepercayaan masyarakat Bali. Proyek ini diharapkan dapat menjadi harapan dan ruang publik yang menyampaikan pengalaman ruang spasial membawa manusia kedalam dimensi yang berbeda, menghargai proses eksplorasi. Menjadi proyek yang dapat memengaruhi psikologis pengunjung akan pentingnya kelangsungan hidup ekosistem laut.